Total fluoride intake in children aged 22–35 months in four Colombian cities - Franco A ´ M, Martignon S, Saldarriaga A, Gonza´lez MC, Arbela´ez MI, Ocampo (Blackwell Synergy, 2005)
To obtain information on the level of total fluoride intake from food, beverages and toothpaste by children at the age of 22–25 months of low and high socioeconomic status (SES) in major Colombian cities